ANALYSIS THE INFLUENCE OF PRODUCT KNOWLEDGE, SALE PROMOTION AND PRICE TOWARDS CONSUMER PURCHASE DECISION AT MEIKARTA CONSUMER IN MANADO - Bysella, Maukar Gita; Lapian, S.L.H.V Joyce; Tumbuan, Willem J.F.A (Universitas Sam Ratulangi, 2018)
Abstract: Meikarta is the largest project ever developed by Lippo Group over the last 67 years. Meikarta will become the largest and most beautiful city in Southeast Asia to provide quality of life and a better place to work. Meikarta comes with a vision to create quality housing at affordable prices, in an effort to help the government reduce the number of home backlog of 11.4 million units. Initial survey showed sales of Meikarta influenced by product knowledge, sale promotion, and price especially in determining consumer purchase decisions. The purpose of this study to determine the effect of product knowledge, sale promotion, and price either simultaneously or partially on consumer purchase decisions at Meikarta Project. The method used associative using multiple linear regression analysis. The study population were 60 respondents who live in the city of Manado. The results show product knowledge, sale promotion, and price simultaneously and partially influence on Consumer Purchase Decision. Meikarta Group Management should increase the value of product attributes by improving product knowledge, sale promotion and price to encourage consumer purchase decisions.Keywords: product knowledge, sale promotion, price, consumer purchase decisionÂ